Have we missed that neural vasodilator mechanisms may contribute to exercise hyperemia at onset of voluntary exercise? - Matsukawa, Kanji; Ishii, Kei; Liang, Nan; Endo, Kana (Frontiers in Physiology, 2013)
Whether neurally mediated vasodilatation may contribute to exercise hyperemia has not been completely understood. Bülbring and Burn (1935) found for the first time the existence of sympathetic cholinergic nerve to skeletal muscle contributing to vasodilatation in animals. Blair et al. (1959) reported that atropine-sensitive vasodilatation in skeletal muscle appeared during arousal behavior or mental stress in humans. However, such sympathetic vasodilator mechanism for muscle vascular bed in humans is generally denied at present, because surgical sympathectomy, autonomic blockade, and local anesthesia of sympathetic nerves cause no substantial influence on vasodilatation in muscle not only during mental stress but also during exercise. On the other hand, neural mechanisms may play an important role in regulating blood flow to non-contracting muscle. Careful consideration of the neural mechanisms may lead us to an insight about a possible neural mechanism responsible for exercise hyperemia in contracting muscle. Referring to our recent study measuring muscle tissue blood flow with higher time resolution, this review has focused on whether or not central command may transmit vasodilator signal to skeletal muscle especially at the onset of voluntary exercise.